Connectional gradients underlie functional transitions in monkey pre-supplementary motor area. (January 2020) - Albertini, Davide; Gerbella, Marzio; Lanzilotto, Marco; Livi, Alessandro; Maranesi, Monica; Ferroni, Carolina Giulia; Bonini, Luca
Graphical abstract: Highlights: F6 encodes location of objects, contextual cues and self/other's action. Functional properties show gradual transitions along the rostro-caudal axis of F6. Cortical and striatal connectivity gradients account for functional transitions. Anatomo-functional gradients may be a basic organizational principle in primates. Abstract: The pre-supplementary motor area F6 is involved in a variety of functions in multiple domains, from planning/withholding goal-directed actions in space to rule-based cognitive processes and social interactions. Yet, the neural machinery underlying this functional heterogeneity remains unclear. Here, we measured local population dynamics in different rostro-caudal sites of cytoarchitectonically verified area F6 in two monkeys during spatial, contextual and motor processes, both in individual and social conditions. Then, we correlated multimodal population tuning with local anatomical connectivity revealed by neural tracer injections into the functionally characterized sites. We found stronger tuning for object position relative to the monkey in the rostral portion of area F6 than in its caudal part, which in turn exhibits stronger tuning to self and other's (observed) action. Functional specificities were associated with a rostro-caudal transition in connectivity strength from lateral prefrontal cortex, pregenual anterior cingulate cortex and associative striatum (rostrally), to dorso-ventral premotor areas and the motor putamen (caudally). These findings suggest that the functional heterogeneity of the pre-supplementary area F6 is accounted for by gradual transitions in functional properties grounded on local cortico-cortical and cortico-striatal connectional specificities.